A review and meta-analysis of interactive metronome training: positive effects for motor functioning - Lee, H. K.; Kim, H. J.; Kim, S. B.; Kang, N. (Perceptual and Motor Skills, 2022)
Interactive metronome training may be effective for improving motor performances through timing. In this systematic review and meta-analysis, 18 prospective studies met our eligibility criteria, and we summarized the effects of interactive metronome training protocols on motor functioning. We estimated effect sizes by quantifying differences in altered motor functions between participants in interactive metronome training and control groups. Two additional subgroup analyses determined whether the positive effects on motor function improvements were different among (a) three types of participants (i.e., athletes, healthy individuals, and patients with neurological disorders) and (b) two different training protocols (i.e., interactive metronome training only and interactive metronome training combined with an additional motor program). Random-effects model meta-analysis revealed moderate positive effects of interactive metronome training on motor function, with interactive metronome treatment effects significant across athletes, healthy individuals, and patients with neurological disorders. Interactive metronome training combined with additional motor programs showed comparable effects to those obtained after interactive metronome training alone. These findings suggest motor improvement benefits to strengthening or capitalizing on an individual`s motor timing.